Constraints to increasing agricultural productivity in Nigeria - Phillip, Dayo; Nkonya, Ephraim M.; Pender, John L.; Oni, Omobowale Ayoola (International Food Policy Research Institute, 2009)
Agriculture is the principal source of food and livelihood in Nigeria, and employs nearly three-quarters of the nation's work force. Over the past two decades, agricultural yields have stayed the same or declined. Although there has been a recent rise in agricultural productivity, it is derived more from expanded planting areas for staple crops than from yield increases. Increasing and sustaining agricultural productivity should be a critical component of programs that seek to reduce poverty and attain food security in Nigeria. This brief presents sector-wide and commodity-specific constraints to increasing agricultural productivity in Nigeria.--Authors' Abstract